Generalize partial Metric spaces - I. Abdullah, Norhan; K. Shaakir, Laith (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2020)
The purpose of this research is to introduce a concept of general partial metric spaces as a generalization of partial metric space. Give some results and properties and find relations between general partial metric space, partial metric spaces and D-metric spaces.